Notes on the orb-weaving spider genus Alpaida (Araneae, Araneidae) with description of four new species from Rio de Janeiro, Brazil - Baptista, Renner Luiz Cerqueira; de Souza Castanheira, Pedro; Prado, André Wanderley Do (Zootaxa, 2018)
Four new species of the orb-weaving spider genus Alpaida O. P.-Cambridge, 1889 from Rio de Janeiro state, Brazil are illustrated and described based on males and females from the following municipalities: Alpaida imperatrix new species (Macaé and Rio de Janeiro); Alpaida imperialis new species (Mendes and Rio de Janeiro); Alpaida marista new species (Mendes and Pinheiral); and Alpaida mendensis new species (Mendes). Furthermore, two new synonymies are herein proposed: Alpaida lanei Levi, 1988 = Alpaida atomaria (Simon, 1895) and Alpaida caxias Levi, 1988 = Alpaida tijuca Levi, 1988, alongside new records for both species and also Alpaida venger Castanheira & Baptista, 2015.